Description of Saccharina japonica commercial stock in the Aniva Bay (Okhotsk Sea) - Natalia M. Aminina; Tatiana I. Vishnevskaya; Dmitry A. Galanin; Anna R. Repnikova; Olga N. Guruleva (Известия ТИНРО, 2014)
Stock of Saccharina japonica in the Aniva Bay (Okhotsk Sea coast of Sakhalin Island) was surveyed by divers in 2010 and assessed with the squares method. The total stock decreased slightly as compared with the previous year (from 47,800 to 43,560 t) but the commercial stock became higher (42,410 t in 2010 against 40,900 t in 2009). The area of traditional harvesting (7.52 km2) was > 80 % covered by the two-years-old algae with total biomass 35,120 t, their highest density (8.9 ind./m², 4.7 kg/m²) was observed in the internal part of the bay. However, the algae in this area had the minimal size parameters (length, thickness, weight), whereas the largest thalli with length 309.7 cm, width 24.2 cm, thickness in the middle strip 3.1 mm, and weight 978.6 g were registered in the external part of the bay. Besides, the algae of the internal part accumulated in their tissues more metals and toxic elements, as calcium, copper, potassium, iron, manganese, zinc, arsenic, lead, and cadmium. The arsenic content in the samples from the internal part varied in the range 0.94-26.60 mg/kg, the highest value was in 5.3 times higher than the maximum permissible level, following to Sanitary Rules and Norms 3.2.1078-01. The content of lead and cadmium did not exceed the established norms, even in the top of the Bay.